Dynamic performance analysis of front-wheel drive hybrid electric vehicle architectures under different real-time operating conditions. (25th March 2022) - Siddharth, B. Raja; Pradeep, D. John; Kumar, Y.V. Pavan; Reddy, Ch. Pradeep; Flah, Aymen
Hybrid electric vehicle technology (HEVT) is emerging as a reliable alternative to lessen the limitations of pure electric vehicles. HEVT uses an electric motor as well as an internal combustion engine, which uses battery power and fossil fuels respectively for vehicle mobility. HEVT shifts vehicle power from fuel-to-battery, battery-to-fuel, or both based on user requirements, terrain conditions, etc. The HEVT can be realised by four architectures, which commonly use front-wheel-based two-wheel-drive systems due to their simple architecture and less-cost when compared to rear-wheel drive systems. For finding an effective architecture under dynamic operating conditions (continuous, pulse-type, and step-up type accelerations), a comprehensive analysis of all architectures is presented in this paper by testing various functionalities, viz., speed (vehicle, engine, motor), power (engine, battery), battery electrical losses, charge patterns, and fuel consumption. The modelling/simulation is done in Simulink and various recommendations are proposed using these comparative results.